Comparison of RELMα and RELMβ Single- and Double-Gene-Deficient Mice Reveals that RELMα Expression Dictates Inflammation and Worm Expulsion in Hookworm Infection - Chen, Gang (Infect Immun, 2016)
Resistin-like molecules (RELMs) are highly expressed following helminth infection, where they impact both the host and helminth. While RELMα (Retnla) impairs helminth expulsion by inhibiting protective Th2 immunity, RELMβ (Retnlb) can promote its expulsion. We employed Retnla(−/−) and Retnlb(−/−) mice to delineate the function of both proteins following infection with Nippostrongylus brasiliensis, a hookworm that infects the lung and intestine. Whereas wild-type (WT) and Retnlb(−/−) mice exhibited equivalent infection-induced inflammation, Retnla(−/−) mice suffered a heightened inflammatory response, including increased mortality, weight loss, and lung inflammation. In the intestine, Retnla(−/−) mice had low parasite egg burdens compared to those of WT mice, while Retnlb(−/−) mice exhibited high egg burdens, suggesting that RELMα and RELMβ have functionally distinct effects on immunity and inflammation to N. brasiliensis. To test the importance of both proteins, we generated Retnla(−/−) Retnlb(−/−) mice. Infected Retnla(−/−) Retnlb(−/−) mice exhibited similar responses to Retnla(−/−) mice, including increased mortality and lung inflammation. This inflammatory response in Retnla(−/−) Retnlb(−/−) mice negatively impacted N. brasiliensis fitness, as demonstrated by significantly lower worm ATP levels and decreased intestinal worm burden and fecundity. Lung cytokine analysis revealed that Retnla(−/−) and Retnla(−/−) Retnlb(−/−) mice expressed significantly increased levels of interleukin-4 (IL-4). Finally, we generated Retnla(−/−) mice on the Rag(−/−) background and observed that the effects of RELMα were abrogated in the absence of adaptive immunity. Together, these data demonstrate that RELMα but not RELMβ significantly impacts the immune response to N. brasiliensis infection by downregulating the Th2 adaptive immune response in the lung, which protects the host but allows improved parasite fitness.